The effect of price bundling on tourists' extra expenditure: a mental budget approach. Issue 20 (18th October 2021) - Cozzio, Claudia; Tokarchuk, Oksana; Maurer, Oswin
ABSTRACT: This is a preliminary study that investigates the effect of the expansion of a bundled holiday package on tourists' extra expenditure. From a theoretical perspective, tourists acquiring packaged holidays tend to incur extra expenditure while on vacation and, in turn, to set a mental budget to avoid overspending. Findings from a quasi-experiment show that tourists are setting the same mental budget for extra expenditure regardless of what is included in the bundle on offer. Resort managers should carefully design mixed-product bundled holiday packages, leaving aside some attractive but non-essential options.